Özel teşebbüs, tekel ve devlet : Türkiye’de cumhuriyet’in kuruluşunda ticaret ve sanayi burjuvazisi - Başaran, Neslişah Leman (My University, 2014)
Bu tez, 1920’lerde Türkiye’de faaliyet gösteren Müslüman-Türk tüccar ve sanayicilerin “burjuvazi” olarak adlandırılabilecek bir sosyal sınıf oluşturduklarını ve ülke ekonomisi, siyaseti ve toplumsal yaşamı üzerinde egemenlik kurmak üzere çalıştıklarını göstermeyi amaçlıyor. Burjuvazi olarak adlandırdığımız bu sosyal sınıfın kökenleri Osmanlı İmparatorluğu’nun 19. yüzyılına dek uzanmaktadır ancak asıl gelişimi 20. Yüzyılın ilk iki on yılında gerçekleşmiştir. Bu yıllarda, Müslüman-Türk tüccar ve sanayiciler ortak kültürel değerlere, ortak bir ideolojiye ve ülke ekonomisine dair ortak görüşlere sahiptir. Bu çalışmada söz konusu sınıfın bileşimi, kimlerden oluştuğu, ekonominin hangi alanlarında faaliyet gösterdikleri, zenginleşme kaynakları gibi konular ele alınmıştır. Bunlarla birlikte, tüccar ve sanayicilerin siyasi ve ekonomik örgütlenmeleri, talepleri, ideolojileri ve siyasi partilere ve siyasi iktidara olan yakınlıkları incelenerek, bu sınıfın 1920’lerde oynadığı role ışık tutulmaya çalışılmıştır.

This thesis aims at demonstrate that Muslim-Turkish merchants and entrepreneurs in Turkey in the 1920’s constituted a social class, namely the national “bourgeoisie” of the country, seeking to dominate economically, socially and politically. This is a social class that had its roots in the economic developments of the 19th century in the Ottoman Empire, however fully developed during the first decades of the 20th century. At the beginning of the Republic, the Muslim-Turkish merchants and industrialists constituted a class which was aware of its common interests and which acted accordingly; They were able to get themselves organized in order to obtain their demands and they were in relation with the government not as individuals, but as organized groups. They had a common culture and ideology, and a vision regarding the economy of the country in general, as will be brought forward in the following pages. On one hand, this study reveals the internal composition of this class, its components, the business sectors they dealt with, the sources of their wealth and their paths of development, whereas on the other hand, it presents the role that this social class played in the 1920’s by focusing on their economic and political organizations, their demands and concerns, their ideology and political affiliations and finally on their relationship with the political power.
Keywords: Endüstri Politikası; Endüstrisi ve Ticaret; Özel Teşebbüs; Sanayi Burjuvazisi; Tarih; Tekel ve Devlet; Türkiye